Innovating for the Better? The Role of Advocacy Group Work Experience for Employee Pay - Christoph Grimpe; Ulrich Kaiser; Wolfgang Sofka (Institute of Labor Economics (IZA), 2018)
How valuable is work experience with advocacy groups, e.g. Greenpeace, for new hires of innovative firms? We integrate strategic human capital with stakeholder theory and suggest that this experience creates scarce human capital (knowledge, skills, abilities) facilitating innovations acceptable and legitimate for stakeholders such as regulators or residents. We argue that such human capital is complementary to firm resources and leads to a value surplus. Individuals with advocacy group work experience can subsequently appropriate at least parts of that surplus through higher salaries. Using matched data for 10,303 employees in Denmark, we find that new hires of innovative firms with advocacy group human capital enjoy salary premiums which are stronger in mature and technologically concentrated firms. Our findings have important implications for HR decision making.
Keywords: J24; J6; C21; 330; resource complementarity; advocacy groups; scarce human capital; stakeholder theory; value creation and capture